2019
DOI: 10.1002/ente.201900796
|View full text |Cite
|
Sign up to set email alerts
|

Prepotassiated V2O5 as the Cathode Material for High‐Voltage Potassium‐Ion Batteries

Abstract: The voltage and capacity of cathodes are critical factors for energy density of batteries. However, the cutoff voltage of cathode materials in potassium‐ion batteries (PIBs) is usually 4.0 V, causing structural transformations in the electrode materials in the course of repeated insertion/extraction of K+ ions with a large radius (1.38 Å). Materials with large interlayer spacing and short ion diffusion paths show promise to overcome this issue. K0.486V2O5 nanobelts, prepared by preinserting K+ ions into V2O5, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…This cathode delivered a capacity of 90 mAh g −1 at 10 mA g −1 in the voltage range of 1.5-3.8 V versus K/K + , good rate capability with a capacity of 60 mAh g −1 at 200 mA g −1 , and good cycling stability with 81% capacity retention after 250 cycles at 100 mA g −1 . [56] It is worth noting that the cutoff voltage of most K x MO 2 rarely exceeds 4 V. [43,46] Recently, Yuan et al [57] reported that the pre-inserted K + ions that partially remained between the V and O layers of V 2 O 5 at a high voltage served as stabilizing species to prevent phase [58] Copyright 2018, Elsevier. b) Typical charge/discharge profile and c) enlarged parts of the ex situ XRD pattern of the K 0.83 V 2 O 5 electrode during the first two cycles at 10 mA g −1 .…”
Section: Existing Challenges and Optimization Strategies Of Layered Vanadium Oxidesmentioning
confidence: 99%
“…This cathode delivered a capacity of 90 mAh g −1 at 10 mA g −1 in the voltage range of 1.5-3.8 V versus K/K + , good rate capability with a capacity of 60 mAh g −1 at 200 mA g −1 , and good cycling stability with 81% capacity retention after 250 cycles at 100 mA g −1 . [56] It is worth noting that the cutoff voltage of most K x MO 2 rarely exceeds 4 V. [43,46] Recently, Yuan et al [57] reported that the pre-inserted K + ions that partially remained between the V and O layers of V 2 O 5 at a high voltage served as stabilizing species to prevent phase [58] Copyright 2018, Elsevier. b) Typical charge/discharge profile and c) enlarged parts of the ex situ XRD pattern of the K 0.83 V 2 O 5 electrode during the first two cycles at 10 mA g −1 .…”
Section: Existing Challenges and Optimization Strategies Of Layered Vanadium Oxidesmentioning
confidence: 99%
“…This review also provides the half-cell/full battery performances of all the organic materials we mentioned. restricts the energy density of K-ion full batteries [51][52][53]. In this case, organic cathode materials with high capacity and potential are essential for KIBs and have become an important topic in the current research.…”
mentioning
confidence: 99%
“…For example, Hironaka et al 73 confirmed that the P2-type KxCoO2 could deliver a high reversible capacity of 60 mAh g -1 between 2.0-3.9 V. Masese et al reported a high voltage (4.3 V vs. K + /K) honeycomb layered cathodes P2-type K2NiCoTeO6 for rechargeable PIBs due to the virtue of its moderately inductive TeO6 6framework 74 , and also attributed to a honeycomb-layered K2Ni2TeO6 cathode with a high average discharge voltage of 3.6 V versus K + /K; and a reversible capacity of about 70 mAh g -1 . Various potassium vanadate compounds, including K2V3O8 and K0.486V2O5, were also reported as novel active materials for K storage with suitable reversible capacity 75,76 . The development of novel layered transition metal oxides cathode materials is still imperative and important for the improvement of PIBs.…”
Section: Layered Transition Metal Oxidementioning
confidence: 99%